Peran Modal Sosial dalam Mewujudkan Civic Engagement Pada Santri Pondok Buntet Pesantren - Wahono, Margi; Budimansyah, Dasim; Malihah, Elly; Fitriasari, Susan; Alami, Fegiano Wulung (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
Community participation in social life is become social capital in the current era of globalization. Social capital, which consists of three main elements, namely: trust, norms and social networks, is an instrument that can be used to promote civic engagement. Islamic boarding schools (Pondok Pesantren) have these three elements which need to be analyzed further. This research adopted a qualitative method with a case study approach at the Pondok Buntet Pesantren in Cirebon Regency. The informants in this research were: Pesantren caregivers, ustadz-ustadzah, and students (santri). Analysis was carried out using the triangulation method. Research findings show that social capital plays a significant role in strengthening students' involvement as citizens. Elements of social capital, such as trust, norms, and social networks, are interrelated in encouraging citizen participation. It can be concluded that the development of social capital by students is the key to promoting civic engagement. However, this research only highlights three elements of social capital, so it is hoped that future research can explore other aspects of social capital that have not been covered in this research.